1997
DOI: 10.1021/bi970159x
|View full text |Cite
|
Sign up to set email alerts
|

The Homodimeric Form of Glycine N-Methyltransferase Acts as a Polycyclic Aromatic Hydrocarbon-Binding Receptor

Abstract: In the rat, cytochrome P4501A1 gene expression is thought to be regulated by several trans-acting factors including the 4S polycyclic aromatic hydrocarbon (PAH)-binding protein, which was recently identified as glycine N-methyltransferase [Raha, A., Wagner, C., MacDonald, R. G., and Bresnick, E. (1994) J. Biol. Chem. 268, 5750-5756]. Glycine N-methyltransferase (GNMT) is one of those unique proteins which exhibit diversity in function. Different subunit configurations are involved in its enzymatic role as a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
(39 reference statements)
2
33
0
Order By: Relevance
“…It regulates the ratio of S-adenosylmethionine to S-adenosylhomocysteine and serves as a folate binding protein (12,13). In addition, GNMT binds carcinogens such as polyaromatic hydrocarbons and aflatoxins and prevents the deoxyribonucleic acid (DNA) adduct formation and cytotoxicity induced by these carcinogens (14)(15)(16). Diminished levels of GNMT were observed in both human HCC cell lines and tumor tissues (17,18).…”
Section: Functional Characterization Of Glycine N-methyltransferase Amentioning
confidence: 99%
“…It regulates the ratio of S-adenosylmethionine to S-adenosylhomocysteine and serves as a folate binding protein (12,13). In addition, GNMT binds carcinogens such as polyaromatic hydrocarbons and aflatoxins and prevents the deoxyribonucleic acid (DNA) adduct formation and cytotoxicity induced by these carcinogens (14)(15)(16). Diminished levels of GNMT were observed in both human HCC cell lines and tumor tissues (17,18).…”
Section: Functional Characterization Of Glycine N-methyltransferase Amentioning
confidence: 99%
“…GNMT, which is primarily expressed in cell cytoplasm (6,9,20), is a polycyclic aromatic hydrocarbon-binding protein (27). Previously, we and other groups showed that if the cells were treated with benzo(a)pyrene, GNMT will be translocated into the nuclei (8,28,29). Because cigarette smoking has been identified as a possible prostate cancer risk factor and GNMT inhibits benzo(a)pyrene-7,8-diol-9,10-epoxide-DNA adduct formation (8), the GNMT expression in the prostate may exert a protective effect for individuals exposed to benzo(a)pyrene and its down-regulation may be an early sign for prostate cancer carcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Preliminary data from our real-time PCR analysis showed that after BaP treatment, CYP1A1 gene expression was reduced by approximately 20% in SCG2-1-1 cells compared with HepG2 cells. 5 Previous research has shown that the tetrameric form of rat GNMT acts as an enzyme and that the dimeric form of rat GNMT is capable of binding with polycyclic aromatic hydrocarbons (39). In this study, we used LGA and a scoring function for estimating binding-related free energy change to locate possible sites for interactions between BaP and various forms of GNMT; we used X-ray crystallography data for rat GNMT for this purpose.…”
Section: Discussionmentioning
confidence: 99%